Ascending combinatorial scoring auctions - Thomas Rieck (University of Bonn, Bonn Graduate School of Economics (BGSE), 2009)
In multi-attribute procurement auctions with multiple objects, the auctioneer may care about the interplay of quality attributes that do not belong to the same item – like each item's delivery time, if all items are needed at once. This can in?uence the performance of the auction mechanism. We generalize the Ausubel-Milgrom ascending proxy auction to such an environment and show that the main properties still hold: Equilibria in pro?t-target strategies exist, the ?nal allocation maximizes the surplus and the payo? vector is in the core. Furthermore, the scoring rule used to evaluate the bids may contain valuable infor- mation about the auctioneer for his competitors, providing an incentive not to reveal it. In our setting, it is possible to keep the scoring rule secret without changing the outcome of the auction. Additionally, for additive scoring rules a close connection to the original proxy auction exists.
Keywords: D44; D82; 330; Multi-object auction; multi-attribute auction; information revelation; Auktionstheorie; Informationsverhalten; Beschaffung; Theorie